Respuesta :

Nayefx

Answer:

c

Step-by-step explanation:

we are given that

[tex] \displaystyle a_{n} = - 3 \: \cdot a_{n - 1} \\ a_{1} = 45[/tex]

we are already given our first term i.e 45

for second term

[tex] \displaystyle a_{2} = - 3 \: \cdot a_{2- 1} [/tex]

simplify substraction:

[tex] \displaystyle a_{2} = - 3 \: \cdot a_{1} [/tex]

since we have [tex]a_1=45[/tex]

substitute:

[tex] \displaystyle a_{2} = - 3 \: \cdot 45[/tex]

simplify multiplication:

[tex] \displaystyle a_{2} = - 135[/tex]

for third term

[tex] \displaystyle a_{3} = - 3 \: \cdot a_{3- 1} [/tex]

simplify Substraction:

[tex] \displaystyle a_{3} = - 3 \: \cdot a_{2} [/tex]

as [tex]a_2=-135[/tex]

substitute:

[tex] \displaystyle a_{3} = - 3 \: \cdot - 135[/tex]

simplify multiplication:

[tex] \displaystyle a_{3} = 405[/tex]

for forth term

[tex] \displaystyle a_{2} = - 3 \: \cdot a_{4- 1} [/tex]

simplify Substraction:

[tex] \displaystyle a_{2} = - 3 \: \cdot a_{3} [/tex]

substitute:

[tex] \displaystyle a_{2} = - 3 \: \cdot 405[/tex]

simplify multiplication:

[tex] \displaystyle a_{2} = - 1215[/tex]

hence,

the first four terms are 45,-135,405,-1215

Step-by-step explanation:

hence,

the first four terms are 45,-135,405,-1215

ACCESS MORE